ECOWAS Protocol on Free Movement of Persons and Cross-Border Dimensions of Armed Banditry in Nigeria - Chibuike Victor Obikaeze; Harriet Omokiniovo Efanodor-Obeten; Bassey Manasseh; Emmanuel Mkpe Inah (Covenant University Journal of Politics and International Affairs, 2023)
The dialectics that have led to explosion of free movement of persons within ECOWAS borders largely constitute a new dimension of security threats in the region. The security threats emanating from incessant human migration within the region have predictably distorted security architecture of Nigeria, thereby posing colossal pressures on the Nigerian armed forces, as well as leading to loss of human lives, properties and financial resources. The study investigated how ECOWAS protocol on free movement of persons and porous borders in West African region orchestrate armed banditry in Nigeria. The work was anchored on Qualitative-Descriptive method of analysis, and ‘inelastic political will’ was adopted as an analytical construct that explains the inability of ECOWAS member governments as well as the Nigerian government to employ sustainable strategies in tackling the ever-changing security threat dimensions within the region. It was revealed that chaotic and explosive cross border migration of persons in West Africa has a relationship with the new dimension of armed banditry in Nigeria. The study recommended that the ECOWAS framework that promotes free movement of people is to be reviewed and amended to address current security crises in the region. Also, there is need for the Nigerian government to reinforce a viable and strong diplomatic tie with the neighbouring countries such as Benin, Chat, Niger and Cameroon regarding border infrastructure development and security enhancement mechanisms to cover ungoverned spaces in the Chad Basin Region.